Non-steroidal anti-inflammatory drug-induced perforation of Meckel’s diverticulum - Kumar, Manish; Khanna, Rahul; Meena, Ram N.; Mishra, Shashi P.; Panigrahy, Panchanana; Anand, Akshay; Kumar, Binod (International Surgery Journal, 2023)
Meckel’s diverticulum (MD) is commonest congenital gastrointestinal anomaly, the common complications associated with MD are hemorrhage, ulceration, intestinal obstruction, diverticulitis, umbilical anomalies, and neoplasm. Perforation of Meckel’s diverticulum is a rare entity and there’s very less documentation regarding the incidence of Meckel’s perforation. MD perforation is usually a life-threatening complication and is associated with high mortality, perforation is usually due to diverticulitis, peptic ulcer disease occurring in the ectopic gastric mucosa which might be present in MD. NSAID intake associated with Merkel’s perforation has been documented in a few studies. NSAID intake and gastric perforation have been well established but a relation between NSAIDs and heterotrophic gastric mucosa of MD has not been documented. With NSAIDs use becoming very common it is, therefore, important to document this association.